Adsorpsi Zat Warna Methylene Blue Menggunakan Karbon Aktif dari Kulit Durian (Durio zibethinus Murr.) - Laura Dwi Rha Hayu; Edi Nasra; Minda Azhar; Sri Benti Etika (Departemen Kimia FMIPA UNP, 2022)
Methylene blue is a basic dye that has cationic properties and used in the coloring industry. Adsorption using activated carbon from durian peel is proven to be able to absorb methylene blue. This study used the batch method which aims to determine the optimum conditions for absorption and maximum absorption of methylene blue using activated carbon from durian peel (Durio zibethinus Murr.). The absorption stages were carried out by varying the pH (2, 3, 4, 5, and 6) and the concentration. (40, 80, 120, 160, 200, 240 and 280) mg/L. The results showed that the optimum conditions occurred at pH 5 and a concentration of 240 mg/L with an absorption capacity of 28.647 mg/g and an absorption percentage of 99.66%. Mechanism the absorption of methylene blue follows the equation Freundlich isotherm with a determinant coefficient (R2) of 0,9874.